Cornual ectopic pregnancy in primary care: a high-risk diagnostic challenge - Abd Rahman, Mohd Aizuddin; Md Hadis, Nur Diyana; Wan Md Asri, Wan Nur Shafiqah (Medicine Specialist Association (FMSA, 2025)
Introduction: Cornual ectopic pregnancy is a rare but lifethreatening variant, accounting for 2-4% of ectopic pregnancies. Due to its ability to grow longer before rupture, it presents a diagnostic challenge, especially in primary care. Early recognition is crucial for maternal safety. Case Presentation: A 34-year-old multiparous woman presented to a primary care clinic with two weeks of minimal per vaginal bleeding and mild lower abdominal pain. She was haemodynamically stable. Abdominal exam showed mild suprapubic tenderness. A transabdominal ultrasound (used due to equipment limitations) revealed a gestational sac in the right cornual region with fetal heart activity and no free fluid. The patient was a chronic smoker. Discussion: Cornual pregnancy can present subtly, even in stable patients. Risk factors such as smoking may impair tubal motility, increasing ectopic risk. Literature shows diagnostic delays are common due to non-specific symptoms. This case underscores the need for high clinical suspicion in early pregnancy with atypical bleeding. While transvaginal ultrasound is preferred, transabdominal imaging may still yield crucial findings in resourcelimited settings. The patient was referred urgently and underwent successful laparoscopic surgery. Primary care physicians must recognise red flags and refer promptly. Conclusion: Cornual ectopic pregnancy is rare but serious. This case highlights the importance of vigilance in primary care to ensure early diagnosis and timely referral, ultimately improving maternal outcomes.